The The Advancement Of Gibran In Political Contestation As Vice President Of The 2024 Election In The Perspective Of Political Ethics Of The Indonesian Nation - Ngudi Astuti; Dewi Setyarini (Journal Of Social Science (JoSS), 2024)
The advancement of Gibran Rakabuming Raka to become Prabowo Subiyanto's Vice President has indeed become a controversy in the political and democratic life in Indonesia. With the issuance of the Constitutional Court (MK) Decision Number 90/PUU-XXI/2023 concerning the Granting of Additional Ownership Experience in the Minimum Age Requirements for Presidential / Vice Presidential Candidates, submitted by a student named Almas Tsaqibbirru Re A. This application was accepted by the Constitutional Court on 3 August 2023. This research uses the theory of ethics (imperative ethics) according to Immanuel Kant, which states that an action is said to be right if it is in line with the principle of obligation relevant to it. Categorical imperative ethics is an absolute command and applies generally. to be all-inclusive, in Ethics it is very clear that the categorical imperative, acts based on obligation. Act according to universal laws, i.e. laws that tend to be accepted by society. The loss of ethics in political life has implications for political practices that are Machavellistic, namely politics as a tool to do everything, good or bad without regard to decency, and norms and apply as positivistic nuances (value-free) and this is very contrary to the ethical values of Pancasila Democracy which is upheld for the Indonesian nation. If someone is running for public office, they should prioritize polite politics and heed the rule of law so that there is peace in living together as citizens in the community.